Bisphenol A in dairy products, amount, potential risks, and the various analytical methods, a systematic review - Mohammad-Hossein Ghahremani; Mahmoud Ghazi-Khansari; Zahra Farsi; Najmeh Yazdanfar; Mahadi Jahanbakhsh; Parisa Sadighara (Food Chemistry: X, 2024)
This systematic study deals with the amount of bisphenol A (BPA) in milk and dairy products, its analytical methods, and risk assessment. Milk is one of the drinks that has a high consumption. Bisphenol A can be present both in raw milk and its amount undergoes changes during the pasteurization process. This review was conducted by searching for the keywords Bisphenol A, BPA milk, dairy product, cheese, cream, butter, yogurt, measurement, detection, and analysis in different databases. The search was done in three databases, Scopus, PubMed and Science Direct. The largest number of studies on the determination of bisphenol A belonged to Asian and European countries. The amount of bisphenol A in milks was observed in the range from ND to 640 ng/mL. Furthermore, the amount of BPA in the tested cheese samples was observed in the ND range up to 6.1 ng/g and in the yogurt samples in the ND range up to 4.4 ng/g. The most used analytical method was based on liquid chromatography. The most used solvent for extraction was methanol or acetonitrile. HQ (Hazard Quotient) was also calculated in some studies. There was no risk in terms of milk consumption due to BPA contamination in extracted data.